[en] FRACTURE RESISTENCE OF THE GRADE R4 STRUCTURAL STEEL AND ITS DEPENDENCE WITH THE QUENCHING TEMPERATURE - ROBERTO ANTONIO ROCO ANTUNEZ (MAXWELL, 2006)
[pt] O presente trabalho apresenta um estudo da influência dos tratamentos térmicos de têmpera e revenido sôbre a resistência à fratura do aço estrutural R4, adotado na fabricação de elos para sistemas de ancoragem de unidade offshore e soldados pelo processo de centelhamento. Corpos de prova do tipo CT foram retirados da região da solda dos elos, usinados com orientação L-R e submetidos a diferentes tratamentos térmicos de têmpera (temperaturas de austenitização de 810, 840, 870 e 900ºC) e revenido (640 e 680ºC), num total de quatro condições microestruturais. Após pré-trincamento em fadiga, os corpos de prova foram submetidos a carregamento monotônico em tração, com o objetivo de se determinar a resistência à fratura do material com base no parâmetro CTOD (Crack Tip Opening Displacement). Os resultados do ensaio de CTOD demonstraram que houve uma redução da resistência à fratura do aço estrutural R4 com o aumento da temperatura de austenitização (810, 840 e 870°C) e temperatura de revenido de 640°C. Entretanto, para maiores temperaturas de austenitização (900°C) e revenido (680°C), houve um aumento do parâmetro CTOD. Modificações microestruturais no material causadas pelos tratamentos térmicos foram associadas com as variações da tenacidade. === [en] This study has been made concerning the influence of quenching and tempering heat treatments on the fracture resistance of a grade R4 structural steel, largely used for fabricating offshore mooring chains by flash welding. CT specimens were taken from the welded joints region in L-R and machined following orientation and subjected to different quenching (austenizing temperatures of 810, 840, 870 and 900ºC) and tempering (640 ºC and 680ºC) treatments, in a total of four microstructural conditions. After fatigue precracking, the specimens were monotonically loaded in tension in order to determine the fracture resistance of the material on the basis of the CTOD (Crack Tip Opening Displacement) parameter. The results of the CTOD tests showed that the fracture resistance of the grade R4 structural steel has decreased when increasing the austenitizing temperature (810, 840 and 870°C) and tempering at 640ºC. However, when adopting higher austenitizing (900°C) and tempering (680° C) temperatures, the parameter CTOD has increased. The microstructural modifications caused by the heat treatments were associated with the toughness modifications.